Comparative efficacy of immunomodulators and sensitive antibiotic on endometrial histopathology in endometritis in crossbred cows - PRASAD, J K; SAXENA, M S; PRASAD, SHIV (The Indian Journal of Animal Reproduction, 2023)
The present study was undertaken to evaluate the efficacy ofimmunomodulators (E.coli LPS & oyster glycogen) andsensitive antibiotic on endometrial histopathology used for treatment of endometritis in crossbred cows. Forty eight cowstested positive for endometritis on the basis of appearance and white side test were randomly divided into 4 groups with 12cows in each group. In group A, I 00 μg of£. coli LPS once, in group B, 500 mg oyster glycogen (OG) once, in group C, mostsensitive antibiotic i.e. enrofloxacin was infused intrauterine for 3 consecutive days and in group D, 20 ml PBS was infusedonce which served as control. Endometrial biopsies were collected at O hour i.e. before treatment and at 72 hours after treatmentfrom all the groups for histopathological study.The incidence of acute/mild type of endometritis was significantly (P
Keywords: Endometritis; immunomodulator; E.coli LPS; oyster glycogen; antibiotics; endometrium; hostopathology; crossbreed cow